دور البرامج المبتكرة في الحد من السرقة العلمية تجارب بعض جامعات المملكة العربية السعودية نموذجا - بايع راسو حنان; بن براهيم فارس; لعجالي سناء (University Of Eloued جامعة الوادي, 2023)
Today's world is experiencing an unprecedented technical and scientific development that is reflected in various fields، Similar to the field of scientific research, but this development did not cover the problems and abuses that accompanied it, on top of which was scientific theft Which has spread widely in academic circles in most universities, both in developing and developed countries, However, this development gave a vision to reduce scientific theft through innovative programs in detecting various types of scientific theft This is what we address in our intervention through the following problems :What is the role of innovative programs in reducing scientific plagiarism? As well as presenting some experiences of Arab universities
The role of innovative programs in reducing scientific plagiarism The experiences of some universities in the Kingdom of Saudi Arabia as a model
مداخلة
Keywords: السرقة العلمية; أخلاقيات البحث العلمي; الانتحال; برامج كشف السرقة العلمية; Scientific theft; Scientific research ethics; plagiarism; Scientific theft detection software